1988
DOI: 10.1152/ajpheart.1988.254.4.h622
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vivo determinations of instantaneous right ventricular pressure and volume in dogs

Abstract: We have developed a method for measuring in vivo canine right ventricular (RV) volume at a frequency of 60 Hz. In six dogs (17-22 kg), under pentobarbital anesthesia, 18 radiopaque markers were surgically implanted in the RV myocardium to maximally represent the RV shell. The xyz-coordinates of the markers were obtained from biplane cineradiographic recordings. RV volume was calculated from the polyhedron created by the markers by decomposing the polyhedron into 24 tetrahedrons, each of whose volumes could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
12
2
Order By: Relevance
“…The ventricular pressure-area loop was not rectangular and was similar to the shape of the mature right ventricle (24,25). The finding that isovolumetric contraction and relaxation phases were short was somewhat different from that of Keller et al (17), who found that there were definite isovolumetric phases during a cardiac cycle in the chick embryonic ventricle.…”
Section: Discussioncontrasting
confidence: 62%
“…The ventricular pressure-area loop was not rectangular and was similar to the shape of the mature right ventricle (24,25). The finding that isovolumetric contraction and relaxation phases were short was somewhat different from that of Keller et al (17), who found that there were definite isovolumetric phases during a cardiac cycle in the chick embryonic ventricle.…”
Section: Discussioncontrasting
confidence: 62%
“…In situ heart 25 RV-Ee, was reported to be 4.14 mm Hg/ml; this value, which was obtained by altering afterload, may be overestimated and somewhat incorrect, 32 although few investigators have examined the effect of afterload on RV-ESPVR. RV-E^ (mean value in small LV volume level, 2.63 mm Hg/ml) in our study is somewhat higher than that in the study of Maughan et al 24 and lower than that of Schwiep et al 25 RV-V 0 (3.92 ml [or 5.92 ml when the 2-ml volume of the balloon wall and hardware was included]) in our study is lower than that of Maughan et al There may be a limitation in our study because we used defibrillated hearts. However, our value of RV-E a was within the physiological range, as found in the previous studies.…”
Section: Discussioncontrasting
confidence: 77%
“…This phenomenon is considered to contribute, at least partly, to the changes in RV-E« and RV-V 0 ( Figure 6). Recently, several authors have investigated RV-ESPVR in isolated dog heart, 1724 in situ dog heart, 25 and human heart. 26 - 28 Maughan et al 24 reported that RV-ESPVR was linear and sensitive to change in the contractile state, as reported for LV-ESPVR.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation used for this study was an anaesthetized, open-chest, this technique for the rabbit RV (Schwiep et al, 1988) and others for the LV (Baan et al, 1984), it is not clear whether animals with larger sized hearts would behave in a similarmanner. Potentially, these young animals might have residual neonatal RV hypertrophy, which might cause them to behave differently.…”
Section: Limitations Of the Studymentioning
confidence: 99%